The Role of Quality Audit Committee Oversight: Quality of Sustainability Reports in Indosesian Energy Sector Companies - Prabowo, Jefry; Hastuti, Sri; Yulianti, Retno (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study examinies the role of audit committee oversight quality on the quality of sustainability reports (SR) of energy sector companies in Indonesia. Using a quantitative research design and secondary data from annual reports and sustainability reports prepared in accordance with Global Reporting Initiative Standards. This study constructs an SR quality index based on the dimention of Theme/Topic completeness (adherence to material GRI indicators). The audit committee variable is proxied by the frequency of audit committee meetings during the fiscal years. The population includes all energy issuers (oil & gas, coal, electricity, renewable energy) listed on the Indonesia Stock Exchange for the period 2021-2024, with the sample determined using purposive sampling techniques and obtaining a sample of 153. Estimation were conducted using regression analysis accompanied by statistical analysis, classical assimption tests, and hypotesting using SPSS statistic 26. The results indicate that a higher frequency of audit committee meetings has a positive impact on SR quality. This study contributes to the literature on sustainability reporting governance in developing countries like Indonesia and offers replicable measurement guidelines for regulator and practitioners.